2007
DOI: 10.1016/j.yexcr.2007.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 regulates melanocyte dendrite formation through activation of PKCζ

Abstract: Prostaglandins are lipid signaling intermediates released by keratinocytes in response to ultraviolet irradiation (UVR) in the skin. The main prostaglandin released following UVR is PGE 2 , a ligand for 4 related G-protein coupled receptors (EP 1 , EP 2 , EP 3 and EP 4 ). Our previous work established that PGE 2 stimulates melanocyte dendrite formation through activation of the EP 1 and EP 3 receptors. The purpose of the present report is to define the signaling intermediates involved in EP 1 and EP 3 -depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…[33][34][35][36] We then measured PGE 2 release from cultured keratinocytes treated by squalene peroxide. Keratinocytes were treated by squalene peroxide mixture (12.5-50 mM) for 24 h. Squalene peroxide dramatically increased PGE 2 release from keratinocytes in a dose-dependent manner (Fig.…”
Section: Effect Of Squalene Peroxide On Melanin Synthesis Of Culturedmentioning
confidence: 99%
“…[33][34][35][36] We then measured PGE 2 release from cultured keratinocytes treated by squalene peroxide. Keratinocytes were treated by squalene peroxide mixture (12.5-50 mM) for 24 h. Squalene peroxide dramatically increased PGE 2 release from keratinocytes in a dose-dependent manner (Fig.…”
Section: Effect Of Squalene Peroxide On Melanin Synthesis Of Culturedmentioning
confidence: 99%
“…However, PGE 2 has a direct effect on melanocyte-mediated post-inflammatory pigmentary responses and melanocyte dendricity showing relevance to skin tanning [27,38].…”
Section: Cyclooxygenase-derived Mediatorsmentioning
confidence: 99%
“…PGF 2α has been found in whole skin and keratinocytes in culture [21,22,47] and has been linked to inflammation, immune responses, pigmentation and hair growth [27,38,48]. The effects of PGF 2α are mediated through the FP receptor found expressed in epidermal cells and melanocytes [49][50][51].…”
Section: Cyclooxygenase-derived Mediatorsmentioning
confidence: 99%
“…5 In addition, prostaglandins (PGs) are key mediators of diverse functions in the skin; and several reports 6,7 have suggested that PGs mediate postinflammatory pigmentary changes by modulating melanin synthesis and melanocyte dendricity.…”
mentioning
confidence: 99%
“…[2][3][4] The two main paracrine melanogenic cytokines, stem cell factor (SCF) and endothelin (ET)-1, have been demonstrated to play pivotal roles in skin pigmentation, including UV-Binduced pigmentation. 5 In addition, prostaglandins (PGs) are key mediators of diverse functions in the skin; and several reports 6,7 have suggested that PGs mediate postinflammatory pigmentary changes by modulating melanin synthesis and melanocyte dendricity.…”
mentioning
confidence: 99%